Time Trends (2012-2020), Sex Differences and Predictors for Influenza Vaccination Uptake among Individuals with Chronic Obstructive Pulmonary Disease in Spain - Fuentes Alonso, Marta; Jiménez García, Rodrigo; López de Andrés, Ana; Zamorano León, José Javier; Carabantes Alarcón, David; Jiménez Trujillo, Isabel; Sanz Rojo, Sara; de Miguel Diez, Javier (My University, 2022)
Background: To analyze time trends, sex differences, and factors associated with influenza vaccination uptake among individuals with COPD in Spain, 2012¿2020. (2) Methods: A cross-sectional study based on data from the European Health Surveys for Spain, 2020 (EHSS2020) and 2014 and from the Spanish National Health Interview Surveys for 2017 and 2012. (3) Results: The study included 65,447 participants. Prevalence of COPD was 5.9% (n = 3855). Overall, the influenza vaccination uptake among COPD patients was 57.8% versus 28.6% for those without COPD (p < 0.001). Men with COPD reported higher uptake than women in all the surveys studied. Neither the crude nor the multivariable analysis showed a significant variation change overtime for people with COPD. However, among those aged <65 years, crude uptake decreased from 2012 to 2020 (39.4% vs. 33.3%; p = 0.039). Over the entire period, men were vaccinated significantly more than women (OR 1.28; 95% CI 1.12¿1.47). Among COPD participants, included in the EHSS2020, independent predictors of vaccine uptake included being male, higher age, reporting no current smoking and suffering cancer or heart disease. (4) Conclusions: In COPD patients, the influenza vaccination uptake is below desirable levels and did not improve from 2012 to 2020. Sex differences are found, with consistent and constant lower uptake among women with COPD. The observed lower uptake among COPD women and patients with unhealthy lifestyle requires increased attention. Keywords: COPD; influenza; vaccine; sex differences; predictors; health survey; uptake; coverage